Comercio Electrónico Y Su Repercusión En La Evasión De Los Tributos De Los Comerciantes Informales Del Cantón Quevedo Año 2023 - Cedeño Andrade, Rosa Jamileth (2025)
The present research addresses the influence of e-commerce and its impact on tax evasion by informal merchants in the Quevedo canton during the year 2023. It analyzes how digital platforms, by facilitating commercial transactions outside fiscal control, contribute to non-compliance with tax obligations. The study used a quantitative methodology to assess the degree of impact of this global phenomenon on tax matters, additionally, it examines the tax culture of informal merchants and the methods they use to evade taxes. The results reveal that e-commerce, while representing a significant opportunity for economic expansion, also poses a challenge for tax administration, especially in informal sectors where oversight is limited. Informal merchants exploit the lack of effective regulations and the difficulty of tracking online transactions to operate outside the tax system, which undermines fiscal revenue and generates unfair competition with formal businesses. Furthermore, digital informality is driven by anonymity and the absence of mandatory registration on digital platforms, weakening the ability of regulatory bodies to enforce sanctions or implement controls.